Leisure Boredom dan Religiusitas: Pengaruhnya terhadap Kecenderungan Adiksi Internet - Azti Verina Noor Azizah Kosasih; Sarbini Sarbini; Agus Mulyana (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
The internet is an unavoidable necessity. There are positive and negative impacts of internet. One of the negative impacts is addiction. Reasons for someone become addicted to the internet including leisure boredom and religiosity. This study aims to determine whether leisure boredom and religiosity have an influence on the internet addiction in students of UIN Sunan Gunung Djati Bandung. The research method used a quantitative causality design which is analyzed using multiple regression. The study was conducted on 265 students recruited using the accidental sampling method. The measurement uses three scales, the Leisure Boredom Scale, The Centrality of Religiosity Scale, then the Internet Addiction Test. The results showed that leisure boredom and religiosity had significant influence on internet addiction. Influence given is 5.3%. This finding indicates that leisure boredom and religiosity affect someone to become internet addicted by 5.3%, Meanwhile, 94.7% of other factors that influence addiction to the internet may still need further research.